Fiber and Antioxidant Activity of Spice Cookies with Local Flour as Functional Food for Elderly - Nunung Cipta Dainy; Wilda Yunieswati; Inne Indraaryani Suryaalamsah (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Older people are vulnerable to infectious and degenerative diseases due to decreased organ function and lowered immune systems. This study aimed to analyze the quality and level of liking of the spice cookies formula and the fiber and antioxidant content of the selected cookies formula. The research method used a factorial complete randomized design with the treatment of wheat flour substitution using arrowroot flour and canna flour. There were three levels of substitution ratio, namely 50:50, 25:75, and 0:100, resulting in six formulas. The variables measured were sensory quality and level of liking using an organoleptic test by 30 semi-trained panelists. Organoleptic test data were statistically analyzed using the Kruskal Wallis test and Mann-Whitney further test. The two best formulas were selected using the exponential comparison method and then analyzed for dietary fiber content and antioxidant activity. The results showed that among the six formulas, there were significant differences in texture and aftertaste of the sensory quality and level of liking (p-value<0,05). The selected formulas were 50:50 substitution ratios of either arrowroot flour or canna flour. Cookies with canna flour substitution had a dietary fiber content of 9,6%, while cookies with arrowroot flour substitution were 7.8%. The antioxidant activity of cookies with canna flour substitution amounted to 9,5 mg/100g, while cookies with arrowroot flour substitution amounted to 12,0 mg/100g. In conclusion, spice cookies with a 50:50 ratio of canna flour and wheat flour substitution have the highest fiber content with strong antioxidant activity.